1968
DOI: 10.1159/000129970
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing mammalian X chromosome condensation and sex chromatin formation

Abstract: The aim of this study is to determine why, in contrast to expectations based on the Lyon hypothesis, a variable number of nuclei of cells from mammalian females are sex chromatin negative. The frequency of sex chromatin positive nuclei was determined in cell cultures of varying cell densities. The cells were derived from seven chromosomally normal human female embryos, one newborn female with an extra E group chromosome and two normal male embryos. In all cultures of females the frequency of sex chromatin posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1970
1970
1986
1986

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Similarly, Therkelsen & Petersen (1967), again working with cultured fibroblasts, plotted curves of the change with time of both G-6-PD activity and sex chromatin count, and found no evidence that cells without sex chromatin had more than one X active. Klinger, Davis, Goldhuber & Ditta (1968) found one cause of the variation in sex chromatin count among cultured cells to be the number of cells per unit volume (cell density), the count increasing with density. After a change in density the sex-chromatin count altered so rapidly that it seemed most unlikely that any change in chromosome activity was involved.…”
Section: -2mentioning
confidence: 99%
“…Similarly, Therkelsen & Petersen (1967), again working with cultured fibroblasts, plotted curves of the change with time of both G-6-PD activity and sex chromatin count, and found no evidence that cells without sex chromatin had more than one X active. Klinger, Davis, Goldhuber & Ditta (1968) found one cause of the variation in sex chromatin count among cultured cells to be the number of cells per unit volume (cell density), the count increasing with density. After a change in density the sex-chromatin count altered so rapidly that it seemed most unlikely that any change in chromosome activity was involved.…”
Section: -2mentioning
confidence: 99%
“…An analysis of the factors controlling the onset of sex chromatin formation in the rabbit (Klinger, Kosseff & Plotnick, 1971) suggested that absolute time from fertilization was the most important single factor, although a lowering of cell metabolism may also be involved (Klinger, Davis, Goldhuber & Ditta, 1968;Issa et al, 1969). It was, therefore, of interest to study the formation of sex chromatin during the development of a species such as the roe deer in which the blastocyst is maintained unattached and metabolically inactive in the uterine lumen for about 5 months (Short & Hay, 1966;Aitken, Burton, Hawkins, Kerr-Wilson, Short & Steven, 1973 In the second group of embryos, the presumptive males, large condensations of chromatin resembling sex chromatin were only observed in 7-6 + 4-5% (mean + S.D.)…”
mentioning
confidence: 99%
“…Control cultures were treated identically except for omission of 5-azaC. Since it has been shown that the frequency of Barr body" 1 " nuclei in cultured human fibroblasts is related to cell density (Klinger et al 1968;Mukherjee & San Sebastian, 1978), the average cell densities for a particular set of treated and control cultures were kept more or less constant by seeding the same number of cells in each culture tube. The cell viability and growth were not adversely affected in the experimental cultures as determined by trypan blue test and by determination of cell numbers at various time intervals.…”
Section: Methodsmentioning
confidence: 99%